Cardiorespiratory Fitness as a Modifiable Target in Scoliosis Surgery: A Narrative Review of Prehabilitation and Perioperative Exercise Interventions - Kozłowska, Jana; Przepióra, Agnieszka; Orłowska, Maria; Żmigrodzka, Anna; Sanocka, Maria; Wielogórska, Aleksandra; Trojnar, Karolina; Czernic-Goławska, Klaudia; Kamińska, Agnieszka; Falana, Joanna; Kwiatkowska, Anna (Quality in Sport, 2026)
Background. Adolescent idiopathic scoliosis (AIS) is associated with clinically significant cardiorespiratory impairment, including reduced peak oxygen consumption, ventilatory inefficiency, and diminished exercise tolerance, even in mild-to-moderate curves. These deficits are compounded by lower habitual physical activity, creating a deconditioning cycle that compromises physiological reserve before surgical correction. Aim. To evaluate current evidence on the relationship between physical activity, cardiorespiratory fitness, and surgical outcomes in AIS, with emphasis on the potential of prehabilitation to optimize perioperative cardiorespiratory function. Material and methods. A narrative literature review was conducted using PubMed, covering studies published between 2003 and 2026. The search combined free-text terms and MeSH headings related to scoliosis, preoperative physical activity, and surgical outcomes. Included study types were randomized controlled trials, systematic reviews, and meta-analyses involving human subjects published in English. Results. AIS patients demonstrate VO2max values reduced by 23% compared to healthy peers, with vigorous physical activity associated with a 24% reduction in AIS odds. Scoliosis-specific exercises reduce curve progression by 70-73%, while surgical prehabilitation reduces pulmonary morbidity by 60% and overall morbidity by 37%. The only AIS-specific prehabilitation RCT confirmed durable cardiopulmonary improvements persisting 12 months postoperatively. Postoperative rehabilitation further enhances respiratory muscle strength, thorax mobility, and quality of life while reducing hospital stay. Conclusions. Evidence supports incorporating cardiorespiratory-targeted exercise in both preoperative and postoperative phases of scoliosis surgery. Large-scale multicenter RCTs with standardized protocols and cardiopulmonary endpoints are urgently needed in the AIS population.